2012
DOI: 10.1186/1471-230x-12-2
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the FIB4 index in a Japanese nonalcoholic fatty liver disease population

Abstract: BackgroundA reliable and inexpensive noninvasive marker of hepatic fibrosis is required in patients with nonalcoholic fatty liver disease (NAFLD). FIB4 index (based on age, aspartate aminotransferase [AST] and alanine aminotransferase [ALT] levels, and platelet counts) is expected to be useful for evaluating hepatic fibrosis. We validated the performance of FIB4 index in a Japanese cohort with NAFLD.MethodsThe areas under the receiver operating characteristic curves (AUROC) for FIB4 and six other markers were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
188
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 317 publications
(213 citation statements)
references
References 35 publications
(45 reference statements)
3
188
1
Order By: Relevance
“…This was in agreement with (Sumida et al, 2012) [21] who conducted this study upon Japanese nonalcoholic fatty liver disease population. This contradict with Sterling et al, 2006 [10] who found that there was statistically significant difference between mild (Ishak score 0 -1), moderate (Ishak score 2 -3) and severe fibrosis (Ishak score 4 -6) as regard the ALT.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This was in agreement with (Sumida et al, 2012) [21] who conducted this study upon Japanese nonalcoholic fatty liver disease population. This contradict with Sterling et al, 2006 [10] who found that there was statistically significant difference between mild (Ishak score 0 -1), moderate (Ishak score 2 -3) and severe fibrosis (Ishak score 4 -6) as regard the ALT.…”
Section: Discussionsupporting
confidence: 90%
“…Claiming that the age has been used in the past-in the absence of knowledge of exact time of disease onset-as a surrogate marker of disease duration and has been associated with more advanced fibrosis [20]. It also contradicts with Sumida et al, 2012 [21].…”
Section: Discussionmentioning
confidence: 98%
“…We used fib-4 index [43] as a marker for liver fibrosis. Among 3,846 participants with fatty liver disease, 9.2% (355 participants) were indeterminate range (FIB-4 index 1.30-2.67) and 0.3% (13 participants) were high-risk (FIB-4 index >2.67).…”
Section: Discussionmentioning
confidence: 99%
“…Sumida et al (12) diagnosed the state of fibrosis in liver biopsies of 576 Japanese patients with NAFLD, and investigated whether such staging could be evaluated with the FIBstudy, the cut-off points for the FIB-4 index was categorized as low at <1.45, indeterminate at 1.45-3.25, and high at >3.25. Compared with other scoring systems, these values were found to be useful for distinguishing between mild and severe fibrosis, with a reported negative predictive value of 98% and positive predictive value of 53%.…”
Section: Discussionmentioning
confidence: 99%